A method for preparing a Fe-MOF / Li6PS5Br composite positive electrode and a full solid-state battery by a wet method
Patent Information
- Application Number
- CN202611212060.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-09
AI Technical Summary
[0021]1.界面传导性能大幅提升:负压湿法浸渍实现电解质全孔隙填充,固 - 固界面接触面积显著提升,电池放电比容量明显高于传统干法电极;
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sulfide solid electrolyte preparation technology, specifically relating to a wet method for preparing Fe-MOF / Li6PS5Br composite cathode and its all-solid-state battery. Background Technology
[0002] introduction
[0003] In liquid batteries, the flowing electrolyte freely permeates into the pores of the porous electrode, forming a good ion conduction network. However, during the assembly of solid-state batteries, the solid electrolyte cannot "automatically" fill the pores of the porous electrode. Therefore, certain methods must be taken before battery assembly to bring the solid electrolyte into contact with the active material in order to form a composite electrode with good ion conduction properties.
[0004] For example, patent CN117832595A discloses a double-layer sulfide electrolyte film prepared by a dry-wet mixing process, which includes: a dry process solid electrolyte base film and a wet process solid electrolyte layer; wherein, the wet process solid electrolyte layer is sprayed onto one side of the dry process solid electrolyte base film by a spraying equipment, and contacts the negative electrode side during solid battery assembly.
[0005] There are roughly three wet-process methods for preparing composite electrodes: one-pot method, slurry method, and impregnation method. Among them, the impregnation method is an emerging method and is considered the most promising for large-scale production by integrating with existing liquid battery electrode sheet production lines. The process involves first fabricating the electrode material into conventional electrode sheets or stacking powders, and then pouring an electrolyte solution over it to fill the gaps. Compared to the first two methods, the biggest advantage of the impregnation method is its wide applicability, as it does not require the solvent and binder to be compatible with both the electrolyte and electrode materials, thus making it highly valuable for research. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing Fe-MOF / Li6PS5Br composite cathode and its all-solid-state battery by wet impregnation: a low-polarity anhydrous ether solvent is used to replace ethanol to avoid the alcoholysis failure of Li6PS5Br; wet negative pressure impregnation ensures that the electrolyte uniformly fills the electrode pores, significantly improving the solid-solid interface contact area and structural stability; boron-based antioxidants construct an inert chemical interface environment, suppressing charge-discharge oxidation side reactions, reducing the decomposition loss of active materials and sulfide electrolyte, and significantly improving the oxidation resistance and long cycle life of sulfide solid-state batteries.
[0007] A. In an anhydrous and oxygen-free argon glove box (water and oxygen content < 0.1 ppm), lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium bromide (LiBr) powders are weighed and mixed and ground according to the mass ratio. The powder is cold-pressed and then vacuum-sealed into a quartz tube. High-purity argon tube furnace is used for high-temperature solid-phase sintering in stages. The sintered block is ground and sieved in the glove box, and then sealed to prevent moisture from entering, thus obtaining pure phase Li6PS5Br solid electrolyte powder.
[0008] B. Disperse Li6PS5Br powder in an anhydrous low-polarity ether solvent under inert conditions and prepare an electrolyte dispersion by stirring in a closed container at room temperature.
[0009] C. Preparation of Composite Cathode: Fe-MOF active powder, conductive carbon black, PVDF binder, NMP solvent, and boron-based antioxidant are mixed evenly according to the specified ratio, coated onto an aluminum current collector with a doctor blade, and dried at low temperature in the first stage to remove NMP; the formed cathode sheet is then impregnated with the above Li6PS5Br dispersion under negative pressure, and dried a second time to remove the organic solvent, yielding the Fe-MOF / Li6PS5Br composite cathode; D. Assembly of All-Solid-State Battery: The composite cathode, Li6PS5Br electrolyte sheet, and lithium metal anode are stacked sequentially, cold-pressed, and packaged. The temperature is measured at 0.045 mA·cm⁻¹ using a constant-temperature electrochemical workstation. -2 Discharge specific capacity and long-cycle capacity retention.
[0010] In a preferred embodiment of the present invention, in step A, the mass ratio of lithium sulfide, phosphorus pentasulfide, and lithium bromide is 18-27:11-33:8.7-26. In a preferred embodiment of the present invention, in step A, the agate powder is ground in a glove box for 10-30 minutes. In a preferred embodiment of the present invention, in step A, a φ8-12mm mold is used, and the pressure is maintained at 300-500MPa for 1-3 minutes to produce 1-3mm round wafers. In a preferred embodiment of the present invention, in step A, the heating rate in a tube furnace is 0.5-5℃ / min, the sintering temperature is 400-600℃, and the holding time is 8-12 hours, with argon protection throughout. In a preferred embodiment of the present invention, in step B, Li6PS5Br and anhydrous ether solvent are mixed in a weight ratio of 5-10:20-30, and stirred in a sealed container at room temperature for 5-8 hours. As a preferred technical solution of the present invention, the mass ratio of CFE-MOF, conductive carbon black, PVDF, NMP, and antioxidant additive is 6~8:1.5~2.5:0.5~1.5:20~30:0.1~0.2.
[0011] As a preferred technical solution of the present invention, the raw materials (parts by weight) for step C, the preparation of the antioxidant auxiliaries, are: 10-20 parts ethylenediamine, 20-30 parts propylene oxide, and 1-2 parts 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester; the preparation process is as follows:
[0012] 1) Add ethylenediamine, propylene oxide, and anhydrous ethanol to a reaction vessel equipped with a reflux condenser and a dropping funnel, and stir at 200-300 rpm for 15-30 min;
[0013] 2) Control the temperature at 50~70℃, slowly add boron ester monomer, keep warm and stir for 3~5 hours, and condense and recover the volatilized propylene oxide;
[0014] 3) Ethanol is removed by vacuum distillation to obtain a borane-modified antioxidant. In a preferred embodiment of the invention, the first drying stage after coating is at 50-100℃ and held for 10-15 hours to remove NMP. In another preferred embodiment, the positive electrode sheet is impregnated with the dispersion under negative pressure for 1-3 minutes, then removed and gradually dried at 80-120℃ for 10-15 hours to remove the ether solvent.
[0015] Reaction mechanism
[0016] 1. Synthesis mechanism of boron-based antioxidant auxiliaries
[0017] Ethylenediamine contains a nucleophilic amino group, and the epoxy ring of propylene oxide is strained, undergoing nucleophilic ring-opening addition in the ethanol system to generate a polyhydroxy amino intermediate. The epoxy group of 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester can undergo secondary ring-opening chain extension with the intermediate amino group, and the electron-deficient boron ester group is grafted onto the molecular backbone. The system is equipped with a condenser to recover the volatilized propylene oxide, and after solvent removal by vacuum distillation, a boron-containing organic antioxidant is obtained. The empty orbitals of boron atoms can capture reactive oxygen free radicals generated during the charging and discharging process, blocking the oxidation chain reaction.
[0018] 2. Mechanism of interface modification by wet impregnation
[0019] Anhydrous ether solvents are used to avoid alcoholysis of Li6PS5Br. The dispersion is penetrated into the micron-sized pores inside the electrode under negative pressure. After drying, Li6PS5Br uniformly coats the surface of Fe-MOF particles, constructing a continuous three-dimensional lithium-ion conduction network, which significantly reduces the impedance at the cathode / electrolyte interface. Boron-based additives are uniformly dispersed inside the composite electrode, forming an inert passivation layer at the two-phase interface, isolating the redox side reactions between the cathode active material and the sulfurized electrolyte, and inhibiting the decomposition of the active material.
[0020] Technical effect
[0021] 1. Significantly improved interfacial conductivity: Negative pressure wet impregnation achieves full pore filling of the electrolyte, significantly increasing the solid-solid interface contact area, and resulting in a battery discharge specific capacity that is significantly higher than that of traditional dry electrode.
[0022] 2. Excellent antioxidant and long-term cycling stability: Boron-based additives capture oxidative free radicals, inhibit interfacial side reactions, and significantly improve the capacity retention rate after thousands of cycles;
[0023] 3. Process adaptability to industrial production lines: The impregnation process is directly compatible with existing coating equipment, the solvent has no sulfide corrosion and decomposition problems, raw materials are readily available, the process window is wide, and mass production feasibility is high;
[0024] 4. Stable material structure: The entire process is prepared in an anhydrous and oxygen-free environment, avoiding the risks of sulfide hydrolysis and oxidation failure. There is no obvious powdering or shedding of the electrode structure during the cycling process. Detailed Implementation
[0025] The present invention will be described in detail below with reference to specific embodiments.
[0026] Example 1
[0027] A wet method for preparing Fe-MOF / Li6PS5Br composite cathode and its all-solid-state battery, characterized by comprising the following steps:
[0028] A. Weigh 18g of lithium sulfide, 11g of phosphorus pentasulfide, and 8.7g of lithium bromide as raw materials for preparing the solid electrolyte. Grind the mixed powder thoroughly for 10 minutes in a glove box. Apply a pressure of 300 MPa using an 8 mm die and hold for 1 minute to press the powder into light yellow discs with a thickness of about 1 mm. Place the discs into quartz glass tubes and vacuum and seal the glass tubes using a tube sealing machine. Place the quartz glass tubes containing the light yellow discs in a tube furnace and heat them to 400℃ at a heating rate of 0.5℃ / min, holding for 8 hours for high-temperature sintering. Remove the discs from the dry glove box, grind them into powder, and package and store them.
[0029] B. Add 5g of Li6PS5Br powder to 20g of anhydrous ethanol and stir thoroughly at room temperature for 5h to obtain an ethanol solution of Li6PS5Br.
[0030] C. Weigh 6g of Fe-MOF powder, 2.5g of conductive carbon, 1.5g of polyvinylidene fluoride, 20g of N-methylpyrrolidone, and 0.1g of antioxidant, mix thoroughly, and coat onto Al foil using a doctor blade method. Dry at 50 ℃ for 10 h. Immerse the above conventional electrode sheet in solution B for 1 min and dry at 80 ℃ for 10 h to obtain Fe-MOF / Li6PS5Br composite cathode material.
[0031] The preparation method of the antioxidant auxiliary agent is as follows:
[0032] Ethylenediamine: 10g
[0033] Epoxy compound propylene oxide: 20g
[0034] 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester: CAS No. 664991-83-7, 1g
[0035] 1) In a reaction vessel equipped with a stirrer, thermometer, and dropping funnel, accurately weighed ethylenediamine and the epoxy compound propylene oxide are added to the solvent ethanol according to the above mass ratio. The stirrer is turned on and stirred at 200 rpm for 15 minutes to ensure that the two are fully dissolved and mixed evenly.
[0036] 2) Accurately measured amounts of 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester were slowly added dropwise to the reaction system through a dropping funnel. The temperature of the reaction system was maintained at 50°C, and the reaction was continued with stirring for 3 hours. The ethanol in the filtrate was removed by vacuum distillation to obtain the borane-modified antioxidant.
[0037] D. Assemble into a lithium / / composite cathode material and test its performance at 0.045 mA cm⁻¹. -2 The discharge capacity at the specified current density is 849.2 mAh g. -1 After 1000 cycles of testing, the capacity retention rate was 67%.
[0038] Example 2
[0039] A wet method for preparing Fe-MOF / Li6PS5Br composite cathode and its all-solid-state battery, characterized by comprising the following steps:
[0040] A. Weigh 23g of lithium sulfide, 22g of phosphorus pentasulfide, and 17g of lithium bromide as raw materials for preparing the solid electrolyte. Grind the mixed powder thoroughly for 20 minutes in a glove box. Apply a pressure of 400 MPa using a φ10 mm die and hold for 2 minutes to press the powder into light yellow discs with a thickness of about 2 mm. Place the discs into quartz glass tubes and vacuum and seal the glass tubes using a tube sealing machine. Place the quartz glass tubes containing the light yellow discs in a tube furnace and heat them to 500℃ at a heating rate of 2.5℃ / min, holding for 10 hours for high-temperature sintering. Remove the discs from the dry glove box, grind them into powder, and package and store them.
[0041] B. Add 7.5g of Li6PS5Br powder to 25g of anhydrous ethanol and stir thoroughly at room temperature for 6.5h to obtain an ethanol solution of Li6PS5Br.
[0042] C. Weigh 7g Fe-MOF powder, 2g conductive carbon, 1g polyvinylidene fluoride, 25g N-methylpyrrolidone, and 0.15g antioxidant, mix thoroughly, and coat onto Al foil using a doctor blade method. Dry at 80 ℃ for 12 h. Immerse the above conventional electrode sheet in solution B for 2 min and dry at 100 ℃ for 12 h to obtain Fe-MOF / Li6PS5Br composite cathode material.
[0043] Ethylenediamine: 15g
[0044] Epoxy compound propylene oxide: 25g
[0045] 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester: CAS No. 664991-83-7, 1.5g
[0046] 1) In a reaction vessel equipped with a stirrer, thermometer, and dropping funnel, accurately weighed ethylenediamine and the epoxy compound propylene oxide are added to the solvent ethanol according to the above mass ratio. The stirrer is turned on and stirred at 250 rpm for 20 minutes to ensure that the two are fully dissolved and mixed evenly.
[0047] 2) Accurately measured amounts of 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester were slowly added dropwise to the reaction system through a dropping funnel. The temperature of the reaction system was maintained at 60°C, and the reaction was continued with stirring for 4 hours. The ethanol in the filtrate was removed by vacuum distillation to obtain the borane-modified antioxidant.
[0048] D. Assemble into a lithium / / composite cathode material and test its performance at 0.045 mA cm⁻¹. -2 The discharge capacity at the specified current density is 879.8 mAh g. -1 After 1000 cycles of testing, the capacity retention rate was 75%.
[0049] Example 3
[0050] A wet method for preparing Fe-MOF / Li6PS5Br composite cathode and its all-solid-state battery, characterized by comprising the following steps:
[0051] A. Weigh 27g of lithium sulfide, 33g of phosphorus pentasulfide, and 26g of lithium bromide as raw materials for preparing the solid electrolyte. Grind the mixed powder thoroughly for 30 minutes in a glove box. Apply a pressure of 500 MPa using a φ12 mm die and hold for 3 minutes to press the powder into light yellow discs with a thickness of about 3 mm. Place the discs into quartz glass tubes and vacuum and seal the glass tubes using a tube sealing machine. Place the quartz glass tubes containing the light yellow discs in a tube furnace and heat them to 600℃ at a heating rate of 5℃ / min, holding for 12 hours for high-temperature sintering. Remove the discs from the dry glove box, grind them into powder, and package and store them.
[0052] B. Add 10g of Li6PS5Br powder to 30g of anhydrous ethanol and stir thoroughly at room temperature for 8h to obtain an ethanol solution of Li6PS5Br.
[0053] C. Weigh 8g of Fe-MOF powder, 1.5g of conductive carbon, 0.5g of polyvinylidene fluoride, 30g of N-methylpyrrolidone, and 0.2g of antioxidant, mix thoroughly, and coat onto Al foil using a doctor blade method. Dry at 100 ℃ for 15 h. Immerse the above conventional electrode sheet in solution B for 3 min and dry at 120 ℃ for 15 h to obtain Fe-MOF / Li6PS5Br composite cathode material.
[0054] Ethylenediamine: 20g
[0055] Epoxylated compound propylene oxide: 30g
[0056] 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester: CAS No. 664991-83-7, 2g
[0057] 1) In a reaction vessel equipped with a stirrer, thermometer, and dropping funnel, accurately weighed ethylenediamine and the epoxy compound propylene oxide are added to the solvent ethanol according to the above mass ratio. The stirrer is turned on and stirred at 300 rpm for 30 minutes to ensure that the two are fully dissolved and mixed evenly.
[0058] 2) Accurately measured amounts of 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester were slowly added dropwise to the reaction system through a dropping funnel. The temperature of the reaction system was maintained at 70°C, and the reaction was continued with stirring for 5 hours. The ethanol in the filtrate was removed by vacuum distillation to obtain the borane-modified antioxidant.
[0059] D. Assemble into a lithium / / composite cathode material and test its performance at 0.045 mA cm⁻¹. -2 The discharge capacity at the specified current density is 917.2 mAh g. -1After 1000 cycles of testing, the capacity retention rate was 88%.
[0060] Comparative Example 1
[0061] A wet method for preparing Fe-MOF / Li6PS5Br composite cathode and its all-solid-state battery, characterized by comprising the following steps:
[0062] A. Weigh 18g of lithium sulfide, 11g of phosphorus pentasulfide, and 8.7g of lithium bromide as raw materials for preparing the solid electrolyte. Grind the mixed powder thoroughly for 10 minutes in a glove box. Apply a pressure of 300 MPa using an 8 mm die and hold for 1 minute to press the powder into light yellow discs with a thickness of about 1 mm. Place the discs into quartz glass tubes and vacuum and seal the glass tubes using a tube sealing machine. Place the quartz glass tubes containing the light yellow discs in a tube furnace and heat them to 400℃ at a heating rate of 0.5℃ / min, holding for 8 hours for high-temperature sintering. Remove the discs from the dry glove box, grind them into powder, and package and store them.
[0063] B. Add 5g of Li6PS5Br powder to 20g of anhydrous ethanol and stir thoroughly at room temperature for 5h to obtain an ethanol solution of Li6PS5Br.
[0064] C. Weigh 6g of Fe-MOF powder, 2.5g of conductive carbon, 1.5g of polyvinylidene fluoride and 20g of N-methylpyrrolidone, mix thoroughly and coat onto Al foil using a doctor blade method, dry at 50 ℃ for 10 h, immerse the above conventional electrode sheet in solution B for 1 min, and dry at 80 ℃ for 10 h to obtain Fe-MOF / Li6PS5Br composite cathode material.
[0065] D. Assemble into a lithium / / composite cathode material and test its performance at 0.045 mA cm⁻¹. -2 The discharge capacity at the specified current density is 801.5 mAh g. -1 After 1000 cycles of testing, the capacity retention rate was 53%.
[0066] Performance Comparison Table
[0067] Group Process characteristics <![CDATA[Initial discharge capacity (mAh・g -1 )]]> 1000-cycle capacity retention Comparative Example 2 Dry mixing, no impregnation, no additives 726.4 41% Comparative Example 1 Wet impregnation, without the addition of antioxidants 801.5 53% Example 1 Wet impregnation + low-content additives 849.2 67% Example 2 Wet impregnation + medium content of additives 879.8 75% Example 3 Wet impregnation + optimal additive ratio 917.2 88%
[0068] Experimental conclusions
[0069] 1. Dry-mixed electrodes do not have wet impregnation to fill the pores, resulting in high interfacial impedance and the worst discharge capacity and cycle stability;
[0070] 2. When only wet impregnation is used and no boron-based antioxidant is added, although the interfacial contact is improved, the oxidation side reaction at the charge-discharge interface continues to consume the active material, and the cycle decay rate is fast.
[0071] 3. Examples 1-3, which simultaneously employ ether-based wet impregnation and boron-based antioxidants, show a significant increase in discharge capacity and retention rate over thousands of cycles. With optimization of additive dosage, impregnation, and sintering process parameters, the performance gradient increases. Example 3 represents the optimal process combination of this invention.
[0072] 4. This invention completely solves the problem of Li6PS5Br alcoholysis by replacing the ether solvent, achieves full coverage of pores by negative pressure impregnation, and uses boron-based additives to suppress oxidation side reactions for a long time. It takes into account both electrode interface conduction and long-term cycle stability, making it suitable for industrial production of all-solid-state lithium batteries.
[0073] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Any simple adjustments, equivalent substitutions, or minor optimizations made to the raw material ratio, sintering temperature, impregnation time, additive dosage, and drying parameters within the core concept and preparation principle of the present invention fall within the scope of protection of the claims of the present invention. The ball milling media, pressing time, vacuum impregnation equipment, and electrochemical testing instrument models not detailed in this invention are all conventional and commonly used technologies in the field, and can be flexibly adjusted by those skilled in the art without creative effort. The Fe-MOF / Li6PS5Br composite cathode prepared by this invention can be widely used in electrochemical devices such as power solid-state lithium batteries, energy storage solid-state batteries, and micro solid-state power supplies, possessing excellent electrochemical performance and value for large-scale promotion.
Claims
1. A wet method for preparing Fe-MOF / Li6PS5Br composite cathode and its all-solid-state battery, characterized in that... Includes the following steps: A. In an anhydrous and oxygen-free argon glove box (water and oxygen content < 0.1 ppm), weigh out lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium bromide (LiBr) powders according to the mass ratio, mix and grind them. After the powder is cold-pressed into a quartz tube, it is vacuum-sealed and sintered in a high-purity argon tube furnace in stages. The sintered block is ground and sieved in a glove box and stored in a sealed container to prevent moisture from entering, thus obtaining pure phase Li6PS5Br solid electrolyte powder. B. Disperse Li6PS5Br powder in an anhydrous low-polarity ether solvent (replacing ethanol to avoid alcoholysis) under inert conditions, and prepare an electrolyte dispersion by stirring in a closed container at room temperature. C. Preparation of composite cathode: Fe-MOF active powder, conductive carbon black, PVDF binder, NMP solvent, and boron-based antioxidant are mixed evenly according to the specified ratio, coated onto aluminum current collector with a scraper, and NMP is removed by low-temperature drying in the first stage; the formed cathode sheet is impregnated with the above Li6PS5Br dispersion under negative pressure, and the organic solvent is removed by secondary gradient drying to obtain Fe-MOF / Li6PS5Br composite cathode; D. All-solid-state battery assembly: Composite cathode, Li6PS5Br electrolyte sheet, and lithium metal anode are stacked sequentially and cold-pressed for encapsulation. The temperature is measured at 0.045 mA·cm⁻ using a constant-temperature electrochemical workstation. 2 Discharge specific capacity and long-cycle capacity retention.
2. The preparation method according to claim 1, characterized in that: Step A: The mass ratio of lithium sulfide, phosphorus pentasulfide, and lithium bromide is 18~27:11~33:8.7~26.
3. The preparation method according to claim 1, characterized in that: Step A: Grind the agate powder in a glove box for 10-30 minutes.
4. The preparation method according to claim 1, characterized in that: Step A: Using a φ8~12mm mold, pressurize at 300~500MPa for 1~3min to produce 1~3mm round pieces.
5. The preparation method according to claim 1, characterized in that: Step A: The heating rate of the tube furnace is 0.5~5℃ / min, the sintering temperature is 400~600℃, the holding time is 8~12h, and argon gas is used for protection throughout the process.
6. The preparation method according to claim 1, characterized in that: Step B: Li6PS5Br and anhydrous ether solvent in a ratio of 5-10 by weight: 20-30.
7. The preparation method according to claim 1, characterized in that: Step B: Stir in a sealed container at room temperature for 5-8 hours, completely isolating the container from air and moisture.
8. The preparation method according to claim 1, characterized in that: Step C: The mass ratio of Fe-MOF, conductive carbon black, PVDF, NMP, and antioxidant additives is 6~8:1.5~2.5:0.5~1.5:20~30:0.1~0.
2.
9. The preparation method according to claim 1, characterized in that: Step C: Preparation of antioxidant auxiliaries. Raw materials (parts by mass): 10-20 parts ethylenediamine, 20-30 parts propylene oxide, 1-2 parts 4-(ethylene oxide-2-ylmethoxy)phenylboronic acid pinacol ester; Preparation process: 1) Add ethylenediamine, propylene oxide, and anhydrous ethanol to a reaction vessel with a reflux condenser and a dropping funnel, and stir at 200-300 rpm for 15-30 min; 2) Control the temperature at 50-70℃, slowly add boron ester monomer, keep warm and stir for 3-5 h, and condense and recover the volatilized propylene oxide; 3) Remove ethanol by vacuum distillation to obtain borane-modified antioxidant auxiliaries.
10. The preparation method according to claim 1, characterized in that: The first drying temperature after coating is 50~100℃, and the temperature is maintained for 10~15h to remove NMP.
11. The preparation method according to claim 1, characterized in that: The positive electrode sheet is impregnated with the dispersion under negative pressure for 1-3 minutes, then removed and dried at a gradient of 80-120℃ for 10-15 hours to remove the ether solvent.